Focus on Authors (Marketing Science, 2013)
Adib Bagh (“ How to Price Discriminate When Tariff Size Matters ”) is an assistant professor with a joint appointment in the departments of mathematics and economics at the University of Kentucky. His research interests include price discrimination using nonlinear pricing mechanisms, game theory, and mathematical economics. Hemant K. Bhargava (“ How to Price Discriminate When Tariff Size Matters ”) is an associate dean and the Jerome and Elsie Suran Professor of Technology Management at the Graduate School of Management, University of California, Davis. He studies business strategy and competition for technology products such as information goods, online services, software, electronic gadgets, media and entertainment goods, and alternative energy technologies. Yuxin Chen (“ The Benefit of Uniform Price for Branded Variants ”) is the Polk Brothers Professor in Retailing and professor of marketing at the Kellogg School of Management, Northwestern University. Currently, he is visiting the China Europe International Business School as the Zhongkun Group Visiting Chair Professor of Marketing. His primary research areas include competitive strategies, database marketing, structural empirical models, Bayesian econometric methods, and behavioral economics. His research has appeared in journals such as Marketing Science, the Journal of Marketing Research, Management Science, and Quantitative Marketing and Economics. Pradeep Chintagunta (“ Editorial—Marketing Science: A Strategic Review ”) is the Joseph T. and Bernice S. Lewis Distinguished Service Professor of Marketing at the Booth School of Business, University of Chicago. He graduated from Northwestern University and has also served on the faculty of the Johnson School, Cornell University. He is interested in studying consumer, agent, and firm behavior. In particular, he is interested in measuring the effectiveness of marketing activities in pharmaceutical markets, investigating aspects of technology product markets, studying online and off-line purchase behavior, and analyzing household purchase behavior using scanner data. Tony Haitao Cui (“ The Benefit of Uniform Price for Branded Variants ”) is an assistant professor of marketing at the Carlson School of Management, University of Minnesota, where he teaches Ph.D., EMBA, MBA, and undergraduate courses. He received a B.Eng. in fluid machinery and fluid engineering, a B.Eng. in industrial engineering, and an IMBA, all from Tsinghua University; he holds an M.S. in operations and information management and a Ph.D. in managerial science and applied economics, both from the Wharton School. His research focuses on behavioral modeling in marketing, behavioral and experimental economics, competitive strategies, distribution channels, pricing, and marketing-operations interfaces. His research has appeared in journals such as Marketing Science, Management Science, and Marketing Letters. He was named the 2011 Marketing Science Institute Young Scholar. Yiting Deng (“ Invited Paper—A Keyword History of Marketing Science ”) is a Ph.D. candidate in marketing at the Fuqua School of Business, Duke University. She received her B.A. in economics, B.S. in statistics, and M.A. in economics from Peking University before joining the Ph.D. program. She also holds a M.S. in statistics from Duke University. Her research interests include social media, advertising, online search, and choices. Dennis Fok (“ Moderating Factors of Immediate, Gross, and Net Cross-Brand Effects of Price Promotions ”) is a professor of applied econometrics at the Econometric Institute, Erasmus University Rotterdam. His research interests are in the fields of marketing and applied econometrics. These interests include modeling choice at an individual level as well as at an aggregated level; furthermore, he is interested in nonlinear panels and simulation-based estimation. He publishes on these topics in journals as Marketing Science, the Journal of Marketing Research, the Journal of Applied Econometrics, and the Journal of Econometrics. Brett R. Gordon (“ Advertising Effects in Presidential Elections ”) is the Class of 1967 Associate Professor of Business at Columbia Business School. He received his Ph.D. in economics from Carnegie Mellon University in 2007 and joined Columbia Business School the same year. His research focuses on empirical industrial organization, with an emphasis on questions pertaining to pricing, innovation, advertising, dynamic oligopoly, and competitive strategy. Rajdeep Grewal (“ Stock Market Reactions to Customer and Competitor Orientations: The Case of Initial Public Offerings ”) is the Irving & Irene Bard Professor of Marketing at the Smeal College of Business at the Pennsylvania State University; he is also the associate research director of the Institute for the Study of Business Markets there. He received his Ph.D. in 1998 from the University of Cincinnati. His research focuses on empirically modeling strategic marketing issues and has appeared in prestigious journals such as the Journal of Marketing, Journal of Marketing Research, Marketing Science, Management Science, Quantitative Marketing and Economics, and Strategic Management Journal. Currently, he serves as an associate editor for the Journal of Marketing Research and an area editor for the Journal of Marketing. Dominique Hanssens (“ Editorial—Marketing Science: A Strategic Review ”) is the Bud Knapp Distinguished Professor of Marketing at the UCLA Anderson School of Management, where he has been on the faculty since 1977. His research focuses on quantitative models that improve our understanding of marketing impact on business performance. From 2005 to 2007, he served as Executive Director of the Marketing Science Institute in Cambridge, MA. In 2010, he was elected a fellow of the INFORMS Society for Marketing Science. Wesley R. Hartmann (“ Advertising Effects in Presidential Elections ”) is an associate professor of marketing at the Stanford Graduate School of Business. He holds a Ph.D. in economics from the University of California, Los Angeles. He is interested in applying and developing econometric techniques to analyze questions relevant to marketing and economics. His current research focuses on dynamic choice contexts, pricing, social interactions, and targeted marketing. John R. Hauser (“ Editorial—Marketing Science: A Strategic Review ”) is the Kirin Professor of Marketing at the MIT Sloan School of Management, where he teaches new product development, marketing management, competitive marketing strategy, and research methodology. He has consulted for a variety of corporations on product development, sales forecasting, marketing research, voice of the customer, defensive strategy, and research and development management. Among his awards include the Converse Award for contributions to the science of marketing and the Parlin Award for contributions to marketing research. He is a founder and principal at Applied Marketing Science, Inc., a former trustee of the Marketing Science Institute, a fellow of INFORMS and of the INFORMS Society of Marketing Science, and serves on many editorial boards. He enjoys sailing, NASCAR, opera, and country music. Csilla Horváth (“ Moderating Factors of Immediate, Gross, and Net Cross-Brand Effects of Price Promotions ”) is an assistant professor of marketing at the Institute for Management Research, Radboud University, Nijmegen, the Netherlands. Her research interests include modeling dynamic marketing processes, branding, self-control, and harmful consumer behavior. She publishes in journals such as the Journal of Marketing Research, International Journal of Research in Marketing, Marketing Letters, and International Journal of Forecasting. Dmitri Kuksov (“ A Model of the “It' Products in Fashion ”) is a professor of marketing at the Naveen Jindal School of Management, the University of Texas at Dallas; previously, he worked at Washington University in St. Louis. He holds a Ph.D. in marketing from Haas Business School of the University of California, Berkeley. His research interests include competitive strategy, markets with incomplete information, consumer communication and networks, branding and product line strategy, and customer satisfaction. He received 2005 Frank M. Bass Dissertation Award; two of his papers were finalists for 2007 John D. C. Little Award, and one was a finalist for INFORMS 2012 Long Term Impact Award. He is an associate editor of Marketing Science, Management Science, and Quantitative Marketing and Economics. Vardit Landsman (“ The Relationship Between DTCA, Drug Requests, and Prescriptions: Uncovering Variation in Specialty and Space ”) is an assistant professor of marketing at the Recanati Business School, Tel Aviv University (Israel), and the Erasmus School of Economics, Erasmus University Rotterdam (the Netherlands). Her fields of interest include the implementation of new modeling approaches to the study of marketing phenomena. Her work involves the study consumer choice and, in particular, the analysis of choice processes within new markets, as well as the study of marketing issues in the context of life sciences. Her work has been published in the Journal of Marketing and Quantitative Marketing and Economics. Carl F. Mela (“ Invited Paper—A Keyword History of Marketing Science ”) is the T. Austin Finch Foundation Professor of Marketing at Duke University, where he teaches brand management and the marketing core. His research focuses on the long-term effects of marketing activity and new media. His articles appear in the Journal of Marketing Research, Marketing Science, the Journal of Marketing, the Harvard Business Review, and t